The role of guest loyalty between satisfaction with service recovery and guest behavior in mountain hotels - Josimović, Milica; Ćoćkalo, Dragan; Radivojević, Nikola (Hotel and Tourism Management, 2024)
Purpose – The purpose of the study is to investigate the role of guest loyalty in the relationship between satisfaction with service recovery (SSR) and consumer citizenship behavior (CCB), as well as dysfunctional customer behavior (DCB) of hotel guests. Methodology – The study was conducted on a sample of 1,324 guests from hotels operating in the Republic of Serbia, Croatia, and Slovenia in mountain tourism. The obtained data were analyzed using an SEM approach. Findings – Loyalty has a mediating role in the relationship between SSR and CCB. On the other hand, loyalty does not have a mediating role in the relationship between SSR and DCB of hotel guests during their stay. Implications – The study has theoretical and practical implications. The theoretical implication is that loyalty forms the foundation for guests’ cognitive and affective responses when they are satisfied with a service recovery; this means that loyalty is a driver of hotel guests’ CCB. In the opposite situation, loyalty does not act as a shock absorber that will mitigate the impact of dissatisfaction with service recovery on the manifestation of DCB. The practical implications are that hotels must prioritize effective service recovery strategies to enhance guest loyalty and encourage CCB while simultaneously reducing the risk of DCB.